2020
DOI: 10.3389/fcimb.2020.00467
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Vaginal Microbiota Composition

Abstract: There is increasing evidence that the composition of a woman's vaginal microbiota significantly influences her sexual and reproductive health, including her risk of miscarriage, preterm birth, HIV and other sexually transmitted infections. Efforts to modulate the vaginal microbiota using antibiotic or probiotic therapy have shown limited lasting or reliable success. To explore the natural dynamics and causal pathways responsible for heterogeneity of vaginal microbiota composition we review the existing literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 72 publications
0
38
0
4
Order By: Relevance
“…Those are, for instance, socioeconomic status, poor access to healthcare services, poor nutrition, hygiene and sexual practices, education, and household income, which have been associated with VMB differences even in very homogeneous study groups (122). Moreover, local epidemics of STI and burden of adverse pregnancy outcomes might also explain population differences in VMB composition across sub-Saharan Africa (10, 55,[123][124][125][126][127]. Studies across Europe, Latin America, and sub-Saharan Africa have suggested that school attendance and school-based sexual and reproductive health programs promote acceptance of care during pregnancy and avoidance of early high-risk sexual activities that might lead to increase susceptibility to BV or other genital infections (128,129).…”
Section: Factors Influencing the Vaginal Diversity And Pregnancy Outcmentioning
confidence: 99%
“…Those are, for instance, socioeconomic status, poor access to healthcare services, poor nutrition, hygiene and sexual practices, education, and household income, which have been associated with VMB differences even in very homogeneous study groups (122). Moreover, local epidemics of STI and burden of adverse pregnancy outcomes might also explain population differences in VMB composition across sub-Saharan Africa (10, 55,[123][124][125][126][127]. Studies across Europe, Latin America, and sub-Saharan Africa have suggested that school attendance and school-based sexual and reproductive health programs promote acceptance of care during pregnancy and avoidance of early high-risk sexual activities that might lead to increase susceptibility to BV or other genital infections (128,129).…”
Section: Factors Influencing the Vaginal Diversity And Pregnancy Outcmentioning
confidence: 99%
“…This is aligned with the endorsed concept in infection biology, in which successful pathogen colonization and infection embodies dynamic interactions between the infecting microbes, host factors, and the microbiome ( 10 ). The vaginal microbiota is a complex microbial ecosystem influenced by environmental and host factors as well as ethnic background ( 11 ). The vaginal microbiota in healthy women consists of over 200 bacterial species, but this ecosystem is generally dominated by Lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the relationship between bacterial diversity and endometriosis is opposite in the gut, where individuals with endometriosis had lower bacterial diversity than controls 60 , 61 . Typically reproductive ‘health’ tends to be associated with a low diversity, Lactobacillus dominant vaginal microbiota (reviewed in 63 ), while gut ‘health’ tends to be associated with a diverse microbiota (reviewed in 64 ). Gut microbiota perturbations have been postulated to contribute to pathogenesis of endometriosis via the regulation of inflammatory processes and estrogen metabolism (reviewed in 65 ), and gut permeability is increased in patients with endometriosis 66 which may contribute to the systemic nature of this condition (reviewed in 67 ).…”
Section: Discussionmentioning
confidence: 99%